How Do Different Psoriasis Management Strategies Impact Quality Of Life In Adult Patients With Chronic Plaque Psoriasis ? : A Systematic Review - Eva Susilawetty Samosir; Eko John Wesley Butar Butar; Malinda R Siburian (The International Journal of Medical Science and Health Research, 2025)
Introduction: Psoriasis, a chronic immune-mediated inflammatory skin disorder, significantly impairs patients' quality of life (QoL) due to erythematous, scaly plaques, pruritus, pain, and psychological distress. The Dermatology Life Quality Index (DLQI) is widely used to assess QoL in psoriasis patients, with higher scores indicating greater impairment. Despite treatment advancements, many patients experience impaired QoL, necessitating effective management strategies. This study systematically evaluates the impact of various psoriasis management strategies on QoL in adult patients with chronic plaque psoriasis, aiming to identify treatments that yield the greatest improvements in symptom relief, daily functioning, and psychosocial well-being. Methods: This systematic review strictly adhered to the PRISMA 2020 guidelines. Studies were screened based on predefined eligibility criteria including adult participants with chronic plaque psoriasis, evaluation of psoriasis management strategies (topical, systemic, biologic, or phototherapy), QoL measurement using validated instruments (e.g., DLQI, SF-36, PSORIQoL), randomized controlled trials or prospective cohort designs, treatment duration of at least 12 weeks, and a sample size of 30 or more participants. Data extraction involved identifying study design, participant characteristics, intervention details, QoL outcome measures, and statistical analyses. A comprehensive search using Boolean MeSH keywords was conducted across multiple databases. Results: Forty studies were included in the systematic review. The majority of studies utilized randomized controlled trial designs (16 studies), with others being observational (8 studies) or pooled analyses/other designs (16 studies). Biologic therapies were examined in 28 studies, small molecule therapies in 5, topical therapies in 3, methotrexate in 2, and phototherapy and spa therapy in 1 each. The DLQI was the most frequently used QoL measurement tool, appearing in 38 studies. Biologic therapies consistently demonstrated the most robust improvements in QoL, with many studies reporting significant DLQI reductions and a high proportion of patients achieving minimal or no impact on QoL (DLQI 0/1). Conventional systemic therapies and combination approaches also showed QoL improvements, including significant symptom relief, particularly pruritus. Improvements were observed across QoL domains such as daily activities, symptom impact, and psychosocial well-being. Discussion: The findings highlight that biologic therapies offer substantial and clinically meaningful improvements in QoL for adult patients with chronic plaque psoriasis, often outperforming conventional systemic treatments. These benefits extend to crucial QoL domains, addressing not only physical symptoms but also psychosocial distress and daily functioning. The consistent reporting of DLQI 0/1 achievement with biologics underscores their efficacy in achieving minimal disease impact on patients' lives. While other treatments also contribute to QoL improvement, biologics appear to offer more comprehensive and sustained benefits. Conclusion: Biologic therapies are highly effective in improving the quality of life for adult patients with chronic plaque psoriasis, demonstrating superior outcomes in symptom relief, daily functioning, and psychosocial well-being compared to conventional systemic treatments. Further research is needed to explore long-term QoL outcomes and patient preferences across different management strategies.